Pengaruh Penggunaan Gadget Terhadap Prestasi dan Hasil Belajar Siswa Sekolah Dasar Negeri 125 Taruna Karya Bandung - Nurfajar, Ilham (Gunahumas, 2023)
Tujuan The purpose of this research was to determine the effect of the use of gadgets on student achievement and learning outcomes. This research uses quantitative methods and analyzed using Statistical Product and Service Solutions. Respondents in this study is 35 students in grade five (V) SDN 125 Taruna Karya Bandung. The results of this research indicate that the frequency of intensity the use of gadgets by students of class V SDN 125 Taruna Karya Bandung tended to be low, as many as 16 respondents and the frequency of the impact of gadget usage on grade V students of SDN 125 Taruna Karya Bandung was classified as moderate, namely as many as 12 respondents and analysis of student learning outcomes of grade V SDN 125 Taruna Karya Bandung is classified as low, with 18 respondents. Based on the results of the questionnaire and the report card score results, it was concluded that the fifth grade students of SDN 125 Taruna Karya Bandung can be said to have no dependency on gadgets